2018
DOI: 10.2147/cmar.s174537
|View full text |Cite
|
Sign up to set email alerts
|

Increased derived neutrophil-to-lymphocyte ratio and Breast Imaging-Reporting and Data System classification predict poor survival in patients with non-distant metastatic HER2+ breast cancer treated with neoadjuvant chemotherapy

Abstract: IntroductionThe prognostic role of the derived neutrophil-to-lymphocyte ratio (dNLR) in human patients with HER2+ breast cancer is not well understood. Here, we aimed to investigate the prognostic significance of dNLR in patients with HER2+ breast cancer undergoing neoadjuvant chemotherapy.MethodsA total of 310 patients with non-distant metastatic HER2+ breast cancer who had received neoadjuvant chemotherapy in our hospital from May 2006 to November 2013 were retrospectively included in this study. Kaplan–Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…Furthermore, only 81 of 155 patients received targeted therapy in this study, with the outcome of worse survival. Findings from a study investigating the prognostic significance of derived NLR in 310 patients who had HER2+ breast cancer and underwent neoadjuvant chemotherapy, amassing a median follow-up time of 62.5 months (9.6–138.5 months) established 270 cases of recurrent or metastatic disease, 246 dead cases, and 16 lost follow-up cases 50. These cases had poor prognoses comparative to those in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Furthermore, only 81 of 155 patients received targeted therapy in this study, with the outcome of worse survival. Findings from a study investigating the prognostic significance of derived NLR in 310 patients who had HER2+ breast cancer and underwent neoadjuvant chemotherapy, amassing a median follow-up time of 62.5 months (9.6–138.5 months) established 270 cases of recurrent or metastatic disease, 246 dead cases, and 16 lost follow-up cases 50. These cases had poor prognoses comparative to those in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Neutrophil-to-lymphocyte ratio (NLR) predicts disease progression and overall survival (OS) in NSCLC patients (22)(23)(24). Derived NLR (dNLR) was used as an alternative to NLR in studies in which lymphocyte count was not available (25) and was shown to predict poor prognosis in both hematologic and solid tumors (26)(27)(28)(29). Although NLR and dNLR were shown to have prognostic value in patients with advanced NSCLC who were receiving ICI (22,23), the biomarkers measured at baseline do not reflect changes in inflammatory status after initiation of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Widmann et al first reported the correlation between the NLR and BC prognosis in 316 patients, and it was found that a higher NLR (≥3.3) before treatment was an adverse factor for both short-and long-term mortality (15). The majority of retrospective studies thereafter have drawn similar conclusions (16)(17)(18)(19), and the NLR was found to be consistent among different BC subtypes at baseline (20,21). However, a prospective substudy of GEICAM/9906, which comprised 1,246 patients, did not find any prognostic value of the NLR after adjustment for clinicopathological factors; in addition, a high NLR was independently associated with worse DFS in only highrisk patients (the hormone receptor-negative/HER2+ population and in patients with ≥3 lymph node metastases) (22).…”
Section: Prognostic Value Of the Neutrophil-to-lymphocyte Ratio (Nlr)mentioning
confidence: 97%